2008
DOI: 10.4314/ajtcam.v4i3.31216
|View full text |Cite
|
Sign up to set email alerts
|

<i>Zizyphus spina-Christi</i> Extract Protects Against Aflatoxin B1- Intitiated Hepatic Carcinogenicity

Abstract: Aflatoxins (AF), a group of closely related, extremely toxic mycotoxins, produced by Aspergillus flavus and A. parasiticus can occur as natural contaminants of foods and feeds. Aflatoxins have been shown to be hepatotoxic, carcinogenic, mutagenic, and teratogenic to different animal species. Zizyphus spina-christi L. extract was investigated for its antifungal and antimicrobial activities. The aim of the present work was to evaluate the antioxidant activity of the methanol extract of Z. spina-christi L. leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 51 publications
10
35
0
1
Order By: Relevance
“…They concluded that Z. spinachristi extract had a markedly protective effect against a flatoxicosis. It is well documented that Z. spina-christi extract is enriched in flavonoid compounds, which can reduce the production of ROS and also show good scavenging activity (Abdel-Wahhab et al (2007). These findings could explain the observed enhancement of the total anti-oxidant capacity and the reduced MDA level in rats treated with Z. spina-christi leaves extract.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…They concluded that Z. spinachristi extract had a markedly protective effect against a flatoxicosis. It is well documented that Z. spina-christi extract is enriched in flavonoid compounds, which can reduce the production of ROS and also show good scavenging activity (Abdel-Wahhab et al (2007). These findings could explain the observed enhancement of the total anti-oxidant capacity and the reduced MDA level in rats treated with Z. spina-christi leaves extract.…”
Section: Discussionsupporting
confidence: 67%
“…The main phytochemical constituents of this plant are including phenolic, flavonoids, alkaloids and saponins (Asgarpanah and Haghighat, 2012). Abdel-Wahhab et al (2007) evaluated the anti-oxidant effect of methanolic Z. spina-christi leaf extract on the oxidative stress of aflatoxin in rats. They reported that the treatment of rats with Z. spina-christi extract significantly improved all biochemical parameters and histological profiles of liver, kidney and testis.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in the architecture of the liver cells could result in the release of certain indicator enzymes in the body. The liver functional transaminases (AST and ALT) and alkaline phosphatase (ALP) enzyme activity in serum are most frequently measured for diagnosis of liver diseases particularly infective hepatitis, alcoholic cirrhosis, biliary obstruction and hepatocarcinoma [3,24]. It has been reported that the normal levels of the former liver functional enzymes activity are up to 37 IU/L for AST, 41 IU/L for ALT and 68-400IU/L for ALP in healthy individual rat sera [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…A növényi kivonat gátolta a CYP 1A1/2 enzimet, amely részt vesz az aflatoxin-B1 bioaktiválásában. A kivonat az aflatoxin-B1 által okozott hepatocarcinogenesis és DNSkárosodás megakadályozását a fázis II enzimek, glutation-S-transzferáz és GSH-peroxidáz aktiválásával éri el [34].…”
Section: Szaponinokunclassified